2019
DOI: 10.1103/physrevd.99.065005
|View full text |Cite
|
Sign up to set email alerts
|

Zero mode suppression of superluminal signals in light-matter interactions

Abstract: We show how two Unruh-DeWitt detectors that do not couple to the zero mode of a quantum field can exchange information faster than the speed of light. We analyze the specific cases of periodic and Neumann boundary conditions in flat spacetime with arbitrary spatial dimensions, and we show that the superluminal signal strength is only polynomially suppressed with the distance to the lightcone. Therefore, in any relativistic scenario modelling the light-matter interaction where a zero mode is present, particle d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Finally it is worth mentioning that non-relativistic, non-local particle detector models are a very common tool and widely used for example in quantum field theory in curved spacetime and relativistic quantum information. Other authors have shown that coupling such a detector model to a finite number of field modes [2] or to all but the zero mode [20] leads to superluminal signalling. In view of our result, this is due to the nonlocality of such a coupling, whereas the detector model sketched at the end of [7] consequently does not signal superluminally.…”
Section: Discussionmentioning
confidence: 99%
“…Finally it is worth mentioning that non-relativistic, non-local particle detector models are a very common tool and widely used for example in quantum field theory in curved spacetime and relativistic quantum information. Other authors have shown that coupling such a detector model to a finite number of field modes [2] or to all but the zero mode [20] leads to superluminal signalling. In view of our result, this is due to the nonlocality of such a coupling, whereas the detector model sketched at the end of [7] consequently does not signal superluminally.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that quantization of a massless scalar field on a topologically closed spacetime and under certain boundary conditions can give rise to zero modes. A zero mode naturally arises when a massless scalar field is subject to periodic or Neumann boundary conditions, or when the background spacetime has toroidal topology in all spatial directions [26][27][28][29][30]. Zero modes are problematic because they do not admit a Fock representation, thus the physical ground state of the zero mode, and hence the full theory, is a priori ambiguous [26,27].…”
Section: Jhep12(2021)170mentioning
confidence: 99%
“…A zero mode naturally arises when a massless scalar field is subject to periodic or Neumann boundary conditions, or when the background spacetime has toroidal topology in all spatial directions [26][27][28][29][30]. Zero modes are problematic because they do not admit a Fock representation, thus the physical ground state of the zero mode, and hence the full theory, is a priori ambiguous [26,27]. For this reason zero modes are sometimes removed by hand [31][32][33][34][35], but such procedure leads to unacceptable causality violations and other issues [27,28].…”
Section: Jhep12(2021)170mentioning
confidence: 99%
See 1 more Smart Citation
“…Having an exactly solvable model allows us to demonstrate explicitly that this non-causal behavior is not an artifact of common approximations employed in such systems-for causality violation in Unruh-DeWitt detectors in a perturbative evaluation, see [62,63]. First, non-causality is not due to the choice of a factorizing initial condition, that was employed in the derivation of the density matrix propagator.…”
Section: The Challenge Of Causalitymentioning
confidence: 99%